2020
DOI: 10.1186/s12877-020-01779-2
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of laparoscopic surgery for colorectal cancer in the elderly aged over 80 years old versus non-elderly: a retrospective cohort study

Abstract: Background Recently, colorectal cancer has increased in elderly patients worldwide, with laparoscopic colorectal surgery increasing in elderly patients with colorectal cancer. However, whether laparoscopic colorectal surgery is an optimal procedure for colorectal cancer in the elderly remains unclear. This study aimed to verify safety and curability of laparoscopic colorectal surgery in elderly patients ≥80 years old. Methods Patients undergoing curative colorectal surgery from 2006 to 2014 were enrolled and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…The complications were similar between LR and OR in this study, except for less blood loss with LR, supported by the general principle of LR (4-8) and by a previous meta-analysis (53) and a cohort study (54). A recent study showed that LR and OR was safe both in elderly and non-elderly patients (55). This lack of difference in complications might play a role in the lack of difference in survival.…”
Section: Discussionsupporting
confidence: 84%
“…The complications were similar between LR and OR in this study, except for less blood loss with LR, supported by the general principle of LR (4-8) and by a previous meta-analysis (53) and a cohort study (54). A recent study showed that LR and OR was safe both in elderly and non-elderly patients (55). This lack of difference in complications might play a role in the lack of difference in survival.…”
Section: Discussionsupporting
confidence: 84%
“…This conclusion is supported by research from Vallribera Valls et al [ 14 ] who demonstrated that laparoscopic approaches in those over 85 are not associated with an increase in morbidity or length of stay. This is also mirrored by more recent studies of Ueda et al [ 15 ] and Hashida et al [ 16 ], both of whom have demonstrated laparoscopic surgery in the elderly population to be feasible, safe and have equitable outcomes to those in younger age brackets.…”
Section: Discussionmentioning
confidence: 67%
“…Over the years, thanks to improvement of anesthesiology and surgical technologies, indications for major surgery have also been extended to the elderly population [ 19 ]. Several studies describe laparoscopic colorectal surgery in elderly patients as technically and oncologically safe compared to non-elderly, with similar results [ 19 , 26 ]. Frasson et al showed how laparoscopic colorectal resection improved short-term postoperative outcome more in elderly than in younger patients [ 13 ].…”
Section: Discussionmentioning
confidence: 95%